EPILEPTIC ENCEPHALOPATHIES WITH ELECTRICAL STATUS EPILEPTICUS OF SLOW-WAVE SLEEP (ESES): DIAGNOSIS AND PHARMACOTHERAPY - A. A. Kholin (Эпилепсия и пароксизмальные состояния)
Electrical status epilepticus of slow sleep (ESES) is a sleep EEG pattern with a continuous (85-100%) diffuse epileptiform activity. The morphology of these epileptiform complexes is identical to benign epileptiform discharges of childhood (BEDC). Epilepsy with ESES (or Penelope Syndrome) is a form of age-dependent epileptic encephalopathies with continuous spike-wave activity during slow wave sleep. This group of epilepsies also includes Pseudo-Lennox syndrome, Landau-Kleffner syndrome, autistic epileptiform regression and some others. Usually, the ESES pattern correlates with the severity of cognitive deficit in epileptic children. The list of anti-epileptic drugs (AEDs) used in pharmacotherapy of epileptic encephalopathies includes valproates, levetiracetam, ethosuximide, sulthiame, topiramate, zonisamide and benzodiazepines; those are given in monotherapy or rationalized combined therapy. Levetiracetam was highly effective in 67.6% of patients with ESES (n=23); among them, two cases of clinical and EEG remission during the pre-puberty period, nine cases of clinical remission and 12 cases with a significant decrease in seizures and epileptiform discharges. In 20.6% of patients (n=7), the pharmacotherapy showed low efficacy. In 11.8% of patients (n=4), aggravation of the disease was noted. Combinations of levetiracetam with valproates and levetiracetam with ethosuximide were found the most effective AEDs. In the cases of epileptogenic structural defect that underlines drug-resistant epilepsy with ESES, neurosurgical intervention is recommended.